Semi‐active adaptive control of stay cable vibrations using MR dampers. Issue 12 (5th October 2022) - Javanbakht, Majd; Cheng, Shaohong; Ghrib, Faouzi
Summary: Among various countermeasures for suppressing bridge stay cable vibrations, installation of external dampers near the lower cable end is the most common practice. Compared to the limitations of passive dampers, especially when attached to superlong cables, semi‐active magneto‐rheological (MR) dampers operated by smart controllers manifest superior control performance. In this study, an adaptive output‐only control scheme is proposed for cable vibration control using semi‐active MR dampers. The controller is designed based on the simple adaptive control (SAC) algorithm. Only one collocated acceleration sensor is used in the control feedback loop. The adverse effect of using acceleration feedback on the control performance is eliminated by adding a stability compensator to the SAC structure. A novel iterative process is formulated to optimize the SAC parameters. The required command voltage of MR damper for generating the control force is obtained by developing a real‐time force tracking strategy. The performance of the proposed control system is evaluated through a numerical example by inspecting the dynamic response of a full‐size stay cable when subjected consecutively to ambient excitation, wind excitation, and free vibration. The robustness of the proposed control scheme against abrupt system changes and contamination in the sensor data are investigated. Results show that the proposed control strategy can effectively mitigate cable vibration under various types of excitation. The controller is proved robust against unexpected changes in the system properties and loads, as well as the presence of sensor noise. Moreover, MR dampers are found to be effective in suppressing multimode cable vibrations.